Linear repetitive process control theory applied to a physical example - Gałkowski, Krzysztof; Rogers, Eric; Paszke, Wojciech (1975- ); Owens, David H. (Zielona Góra: Uniwersytet Zielonogórski)
In the case of linear dynamics, repetitive processes are a distinct class of 2D linear systems with uses in areas ranging from long-wall coal cutting and metal rolling operations to iterative learning control schemes.
Keywords: repetitive dynamics; metal rolling; LMIs; delay differential system; stability